측두하악관절강에 발생한 평활근종에 대한 사례보고와 문헌고찰 - 박승민; 전상미; 김옥준 (대한구강악안면병리학회지, 45(1), 2021)
Leiomyoma is a Benign tumor that develops in smooth muscles and is known to occur more in women in age between 40s and 50s. The most common site of leiomyoma is uterine (95 %). It occurred in oral region is very rare about 0.065 % and usually developed in upper and lower lips, palatal site, buccal site and tongues. The prognosis of leiomyoma is very positive. The recurrence rate is extremely low to 2 % below. In present study, we report a 78 year old female with a lesion located in temporomandibular joint cavity which was suspected as a malignant tumor. Additionally, this paper reports contains a literature review of oral leiomyoma. Rare location with painless leiomyoma of present case will be considered to be caution. KCI Citation Count: 0